Analisis Spasial Tingkat Kekritisan Lahan di Sub Das Wimbi, Kelurahan Sawidago Kecamatan Pamona Utara, Kabupaten Poso - Mangela, Debora; Muis, Hasriani; Rahman, Abdul; Naharuddin, Naharuddin; Massiri, Sudirman Daeng; Maiwa, Arman; Paramitha, Tirtha Ayu; Istiqamah, Nurul (Savana Cendana, 2024)
Critical land currently refers to a number of areas that are significantly unproductive as a result of inadequate management and utilization of soil and water conservation requirements. Critical land is land inside and outside the forest area that has declined in function. Das is a land area bounded by mountain ridges topographically, which functions as a natural reservoir to collect and store rainwater. To identify critical land, weighting and scoring were carried out on several critical land parameters including land cover, slope, and erosion hazard level, which were then overlaid and produced a critical land map. From this research, it was found that Wimbi Sub Das has a distribution of critical land dominated by not critical with an area of 129 ha or with a percentage of 7.12%, potentially critical with an area of 628 ha or with a percentage of 34. 64%, critical with an area of 821 ha or with a percentage of 42.28%, critical with an area of 221 ha or 12.19%, and very critical with an area of 14 ha or 0.77%, Based on the table overlay results show that Sub Das Wimbi is dominated by the level of criticality of the land category with an area of 821 ha which on a global scale has reached an alarming value. So it can be concluded that Wimbi Sub Das shows a rather critical potential, where land with a rather critical potential has an area of 821 ha.